2007
DOI: 10.1002/mrc.2051
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of metabolites from dihydromyricetin

Abstract: Dihydromyricetin (DHM) is the major bioactive constituent of Rattan Tea, which is the tender stems and leaves of Ampelopsis grossendentata. Seven metabolites (2-8) of DHM (1) were obtained by the chromatographic method. The metabolites 2-5 were obtained from the urine of rats administered orally with DHM; and metabolites 6-8 were detected in the fecal specimens of rats, which were also produced by human intestinal bacteria (HIB) in vitro, and were separated from the cultured media of HIB containing DHM. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 7 publications
(7 reference statements)
5
51
0
Order By: Relevance
“…While both 2 R ,3 S and 2 S ,3 R enantiomers were eliminated based on the coupling constant of the signals for H-2 and H-3. The two proton signals of 1 were double and double peaks: 4.81 (1H, J = 10.45 Hz, 2-H), 4.16 (1H, J = 10.6 Hz, 3-H), whereas in its 2 R ,3 S isomer they were both single peaks, which indicated that 2-H and 3-H are either 2 R ,3 R or 2 S ,3 S enantiomers [27]. The experimental ECD spectrum showed a positive Cotton effect at 197 nm and a negative Cotton effect at 217 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While both 2 R ,3 S and 2 S ,3 R enantiomers were eliminated based on the coupling constant of the signals for H-2 and H-3. The two proton signals of 1 were double and double peaks: 4.81 (1H, J = 10.45 Hz, 2-H), 4.16 (1H, J = 10.6 Hz, 3-H), whereas in its 2 R ,3 S isomer they were both single peaks, which indicated that 2-H and 3-H are either 2 R ,3 R or 2 S ,3 S enantiomers [27]. The experimental ECD spectrum showed a positive Cotton effect at 197 nm and a negative Cotton effect at 217 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Dose 1 group received 150 mg/kg of dihydromyricetin every day, and the Dose 2 group received 300 mg/kg of dihydromyricetin every day. At the termination of the study, the mean volumes of the tumors were 1,957 mm 3 for the control group, 1,238 mm 3 for the Dose 1 group, and 834.6 mm 3 for the Dose 2 group (Fig. 3A).…”
Section: Dihydromyricetin Exerts Antitumor Activity In Vivomentioning
confidence: 96%
“…Ampelopsis grossedentata, a vine plant in South China, is a popular and multipurpose traditional Chinese medicinal herb and has a long history of being used as food and medicine (3). Dihydromyricetin, a 2,3-dihydroflavonol compound, is the main bioactive component extracted from Ampelopsis grossedentata, is one kind of flavonoids that has many biologic effects, including antialcohol intoxication, reducing blood pressure, antibacterial, antioxidant, and antitumor properties (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Dihydromyricetin (DHM) is a kind of bioactive flavonoids and identified as the benefit constituent in the tender stems and leaves of Ampelopsis grossendentata (Zhang et al, 2007a). Pharmacokinetic studies of dihydromyricetin and myricetin in rat plasma by High Performance Liquid Chromatography with Diode Array Detector (HPLC-DAD) also have been assessed after oral administration of Ampelopsis grossedentata (Zhang et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%